Mercury removal from wastewater by electrocoagulation - Norain, Shahrom (2012)
In the present study,electrocoagulation was used for the treatment of synthetic solutions containing mercury(II). Study was performed based on synthetic petrochemical waste contaminated with mercury and heavy metals.The objectives of this study are to investigate the efficiency of electrocoagulation in removal of synthetic mercury through and Aluminium electrode and to remove mercury ion from mercury synthetic by electrocoagulation using Aluminium as electrode.In this study equipment such as electrocoagulation OT-1 was used to run the experiment. Three parameters were investigated in this research,which are the effects of the distance between the electrodes,charge loading on the removal efficiency and flowrate.Determination of the Mercury (II) ions was performed by Mercury Analyzer.In this research, in was found that the electrocoagulation result was contribute 99% above removal by using Aluminium as electrode.The research showed the applicability of electrocoagulation to treat water contaminated by mercury. More than 99% of the pollutant was eliminated by using Aluminium as electrodes.The distance between the electrodes gives highest removal was 5 cm.While the lowest concentration is 2ppm with the highest charge loading will be contributes to the higher percentage of removal of mercury up to 99.18%.